Occupational and leisure time physical activity in contrasting relation to ambulatory blood pressure - Clays Els; De Bacquer Dirk; Van Herck Koen; De Backer Guy; Kittel France; Holtermann Andreas (BMC, 2012)
Abstract Background While moderate and vigorous leisure time physical activities are well documented to decrease the risk for cardiovascular disease, several studies have demonstrated an increased risk for cardiovascular disease in workers with high occupational activity. Research on the underlying causes to the contrasting effects of occupational and leisure time physical activity on cardiovascular health is lacking. The aim of this study was to examine the relation of objective and self-report measures of occupational and leisure time physical activity with 24-h ambulatory systolic blood pressure (BP). Methods Results for self-reported physical activity are based on observations in 182 workers (60% male, mean age 51 years), while valid objective physical activity data were available in 151 participants. The usual level of physical activity was assessed by 5 items from the Job Content Questionnaire (high physical effort, lifting heavy loads, rapid physical activity, awkward body positions and awkward positions of head or arms at work) and one item asking about the general level of physical activity during non-working time. On a regular working day, participants wore an ambulatory BP monitor and an accelerometer physical activity monitor during 24 h. Associations were examined by means of Analysis of Covariance. Results Workers with an overall high level of self-reported occupational physical activity as well as those who reported to often lift heavy loads at work had a higher mean systolic BP at work, at home and during sleep. However, no associations were observed between objectively measured occupational physical activity and BP. In contrast, those with objectively measured high proportion of moderate and vigorous leisure time physical activity had a significantly lower mean systolic BP during daytime, while no differences were observed according to self-reported level of leisure time physical activity. Conclusions These findings suggest that workers reporting static occupational physical activities, unlike general physically demanding tasks characterized by dynamic movements of large muscle groups, are related to a higher daily systolic BP, while high objective levels of moderate and vigorous leisure time physical activity are related to lower daytime systolic BP. Ambulatory systolic BP may be a physiological explanatory factor for the contrasting effects of occupational and leisure time physical activity.